Big data and innovation in tourism, travel, and hospitality managerial approaches, techniques, and applications - Rahimi, Roya; Sigala, Marianna; Thelwall, Mike (Springer Singapore Imprint: Springer, 2019)
"This book brings together multi-disciplinary research and practical evidence about the role and exploitation of big data in driving and supporting innovation in tourism. It also provides a consolidated framework and roadmap summarising the major issues that both researchers and practitioners have to address for effective big data innovation. The book proposes a process-based model to identify and implement big data innovation strategies in tourism. This process framework consists of four major parts: 1) inputs required for big data innovation; 2) processes required to implement big data innovation; 3) outcomes of big data innovation; and 4) contextual factors influencing big data exploitation and advances in big data exploitation for business innovation." --